Burnout Management To Maintain The Performance Of The Shipping Crew - Abdul Nasir Rachman; Hardiyono Hardiyono; Ifah Finatry Latiep (Universitas Kristen Indonesia Toraja, 2022)
Burnout is something that must be considered from crew members who have a high workload and maintain their performance. This study aims to analyze the burnout conditions of the crew of the Mutawa 303 while working on board the ship and find solutions so that performance can still be optimized. This research is a qualitative research that examines the conditions that occur in the field from information obtained based on interviews with the captain and crew to identify respondents' perceptions of workload conditions and work-life balance when sailing. The results showed that the burnout experienced by the crew of the Mutawa 303 was in the high category, but the crew tried to work professionally and maintain work-life conditions. balance by regularly communicating through meedia social with family and avoiding role conflicts when sailing which is prone to occur when the crew experiences burnout.